Who is AC? - Larson, Hope (Atheneum Books for Young Readers, 2013)
"Meet Lin, an average teenage girl who is zapped with magical powers through her cell phone. But just as superpowers can travel through the ether, so can evil. And as Lin starts to get a handle on her powers (while still observing her curfew!) she realizes she has to go head to head with a nefarious villain who spreads his influence through binary code"--Provided by publisher.